2021
DOI: 10.1097/jxx.0000000000000586
|View full text |Cite
|
Sign up to set email alerts
|

Use of social determinants of health codes in home-based primary care

Abstract: Background: The Affordable Care Act created funding for nurse practitioner education programs to transform the primary health care workforce through student awareness of how social, political, economic, and environmental factors influence individual and population health. Funding established Academic Clinical Partnerships (ACPs) that created value-based health care models, which improved patient outcomes and decreased hospital and emergency department admissions and health care costs. The ACP estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It is known that SDOH impact healthcare outcomes, and our findings reflect that NPs assess for them routinely (Coppa et al, 2021; Hill-Briggs et al, 2020; New England Journal of Medicine Catalyst, 2017). Although assessment was at 100%, there were multiple limitations to proper screening related to documentation.…”
Section: Implications For Practicesupporting
confidence: 53%
See 1 more Smart Citation
“…It is known that SDOH impact healthcare outcomes, and our findings reflect that NPs assess for them routinely (Coppa et al, 2021; Hill-Briggs et al, 2020; New England Journal of Medicine Catalyst, 2017). Although assessment was at 100%, there were multiple limitations to proper screening related to documentation.…”
Section: Implications For Practicesupporting
confidence: 53%
“…Grade A evidence supports the assessment of social determinants of health (SDOH) and referral to appropriate resources in diabetes management (ADA, 2022). Evidence now indicates that SDOH can be viewed as the strongest predictor of health outcomes at the individual and population level (Coppa et al, 2021; Hill-Briggs et al, 2020; New England Journal of Medicine Catalyst, 2017). Despite this knowledge, the COVID-19 pandemic has exacerbated existing disparities and increased the complexity of chronic disease management, with diabetes being the most affected condition (Chudasama et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are potential benefits to documenting social needs with SDOH-related Z codes, to date, this has not been mandated 2 ; for example, a small review of records for high-risk patients found that 92% of patients had information that could have been coded but were not documented with SDOH-related Z codes. 36 There are efforts to increase the documentation of social needs with SDOH-related Z coding in clinical practice. The AHA recently updated guidance to recommend that administrators raise awareness and educate physicians, other healthcare providers, and medical coders on how to screen, document, and code data on patients’ social needs.…”
Section: Discussionmentioning
confidence: 99%
“…To design the TARGET segmentation tool as truly holistic, it should be expanded with social data, as acknowledged by other studies into segmentation tools as well [ 48 ]. However, these data are often lacking as the internationally classified codes for registering social issues, Z-codes, are systematically underutilized by healthcare professionals and exchange of patient information between domains is complicated [ 17 , 49–52 ]. Instead, the PCAM can be used for registering social data: we recently found evidence that PCAM has adequate measurement properties [ 34 ].…”
Section: Discussionmentioning
confidence: 99%